Natural abundance oxygen-17 solid-state NMR of metal organic frameworks enhanced by dynamic nuclear polarization. Issue 3 (14th January 2021) - Carnevale, Diego; Mouchaham, Georges; Wang, Sujing; Baudin, Mathieu; Serre, Christian; Bodenhausen, Geoffrey; Abergel, Daniel
Abstract : The 17 O resonances of zirconium-oxo clusters that can be found in porous Zr carboxylate metal–organic frameworks (MOFs) have been investigated by magic-angle spinning (MAS) NMR spectroscopy enhanced by dynamic nuclear polarization (DNP). Abstract : The 17 O resonances of zirconium-oxo clusters that can be found in porous Zr carboxylate metal–organic frameworks (MOFs) have been investigated by magic-angle spinning (MAS) NMR spectroscopy enhanced by dynamic nuclear polarization (DNP). High-resolution 17 O spectra at 0.037% natural abundance could be obtained in 48 hours, thanks to DNP enhancement of the 1 H polarization by factors ε ( 1 H) = S with / S without = 28, followed by 1 H → 17 O cross-polarization, allowing a saving in experimental time by a factor of ca. 800. The distinct 17 O sites from the oxo-clusters can be resolved at 18.8 T. Their assignment is supported by density functional theory (DFT) calculations of chemical shifts and quadrupolar parameters. Protonation of 17 O sites seems to be leading to large characteristic shifts. Hence, natural abundance 17 O NMR spectra of diamagnetic MOFs can thus be used to probe and characterize the local environment of different 17 O sites on an atomic scale.